If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = 6(x + -6) Reorder the terms: -2 = 6(-6 + x) -2 = (-6 * 6 + x * 6) -2 = (-36 + 6x) Solving -2 = -36 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -2 + -6x = -36 + 6x + -6x Combine like terms: 6x + -6x = 0 -2 + -6x = -36 + 0 -2 + -6x = -36 Add '2' to each side of the equation. -2 + 2 + -6x = -36 + 2 Combine like terms: -2 + 2 = 0 0 + -6x = -36 + 2 -6x = -36 + 2 Combine like terms: -36 + 2 = -34 -6x = -34 Divide each side by '-6'. x = 5.666666667 Simplifying x = 5.666666667
| X^4+4x^3+6x^3+4x+5=0 | | x^3+x^2-16x+64=0 | | 7y^2=56 | | 2x^3+5x^2-2x-5=0 | | P(x)=x^5+9x^3 | | 3x+4=2x-7 | | 18x^2-21x=0 | | 32x^2-9x-33=0 | | 6(8y-3)-8(3y-6)= | | 25m^2-20m+4=0 | | 8x-40y=4 | | 2x+12=26 | | 12y-17y= | | 25x+5=40 | | -36k+9=-18k | | 12y-56=8y | | -12n-18=-6n | | 3x^12+20x^6+6=0 | | 8x+3x-3x-8=3x | | 8x-10y=-80 | | y=x+17 | | -7=-.4x+4 | | 3=-12n-8 | | 36x^2-36=0 | | y=-.4(-.4)+4 | | y=-.4*4+4 | | 7=-.4*4+4 | | (4x+1)(2x+1)=0 | | 2x-x+3x=-28 | | (4x-1)(2x-1)=0 | | 7=1.14285714286(-39.2)-8 | | 6x-4(1.14285714286x-8)=-24 |